Aqueous nickel sequestration and release during structural Fe(ii) hydroxide remediation: the roles of coprecipitation, reduction and substitution. Issue 88 (7th September 2016) - Shao, Binbin; Chen, Ying; Wu, Deli; He, Hongping; Dai, Chaomeng; Zhang, Yalei
Abstract : SFH has a strong potential for reducing aqueous Ni 2+ and the release of precipitated Ni(ii ) into solution could be controlled. Abstract : Aqueous Ni 2+ removal by structural Fe(ii ) hydroxides (SFH) under well-controlled experimental conditions was investigated in this study, and a possible mechanism for Ni 2+ release from solid products was revealed. Experiments with SFH and Ni 2+ showed the excellent reactivity of SFH towards aqueous Ni 2+ when the molar ratio of [Fe(ii )]/[OH − ] was below 1 : 2. The reaction started with adsorption and precipitation of Ni 2+, followed by reduction of Ni(ii ) and substitution of Fe(ii ) with the formation of Ni(ii )/Fe(iii ) layered double hydroxides. However, at long reaction time, Ni(ii ) release from Ni(OH)2 and Ni x Fe(1− x ) (OH)2 precipitates was observed due to the delivery of dissolved Fe 2+ and Fe 3+, which were determined to substitute Ni(ii ) by forming Fe(OH)2, Fe(OH)3 and Fe III (1+2 x /3) Fe II (1− x ) (OH)5 . The presence of O2 and NO3 − reduced the removal efficiency of Ni 2+ and promoted its release by consuming Fe(ii ) and promoting Fe 3+ delivery. However, CO3 2− and PO4 3− might enhance the removal of Ni 2+ and inhibit its release. For wastewater containing a high Ni 2+ concentration, using SFH is also beneficial to Ni 2+ recycling, as removed Ni(ii ) could be released and enriched, followed by future utilization.